2020
DOI: 10.5222/tp.2020.43153
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Lung Functions Using Tidal Breath Analysis in High-risk Infants with Recurrent Wheezing

Abstract: INTRODUCTION: We aimed to investigate lung functions using tidal breath analysis (TBA) in high-risk infants with recurrent wheezing. METHODS: Lung functions measured using TBA in infants with physician-diagnosed recurrent wheezing (≥3 episodes) who applied our institution between 2018-2020, were retrospectively analyzed. Infants were assigned to two groups: high-risk infants with recurrent wheezing (n=30) and wheezy infants without high risk of atopy (n=33). RESULTS: High-risk infants with recurrent wheezing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…Therefore, the authors are unable to establish whether the differences in TFV loop parameters, including the time and volume ratios, between the awake and sleeping states will remain stable or change with increasing age and decreasing respiratory rate. In a study by A nık and U ysal [ 32 ], the authors found a positive correlation between age and t PTEF / t E ratio among awake infants and children aged 8–23 months with recurrent wheeze, with or without high risk of atopy. Therefore, the generalisability of our findings, differences and similarities, may be limited to TFV loop measurements in young infants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors are unable to establish whether the differences in TFV loop parameters, including the time and volume ratios, between the awake and sleeping states will remain stable or change with increasing age and decreasing respiratory rate. In a study by A nık and U ysal [ 32 ], the authors found a positive correlation between age and t PTEF / t E ratio among awake infants and children aged 8–23 months with recurrent wheeze, with or without high risk of atopy. Therefore, the generalisability of our findings, differences and similarities, may be limited to TFV loop measurements in young infants.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to asthma in adolescents and adults, a previous study of 95 individuals found no differences in TEWL between allergic asthmatics and healthy controls [50]. Infants and children with obstructive airway diseases generally reach tPTEF earlier in the expiratory phase with a subsequent lower tPTEF/tE ratio, compared to healthy children [39][40][41], providing an important rationale for including tPTEF as an outcome in this study. Although reduced skin barrier function was not associated with lower lung function measured by tPTEF/tE, the inverse association with tPTEF, where high TEWL increased the risk for having shorter time before reaching peak expiratory flow, suggests that lung function and skin barrier function may share a common developmental origin, be manifestations of barrier dysfunction observed in two different organ systems, or infer a causal link between the two.…”
Section: Tewl and Lung Functionmentioning
confidence: 83%
“…Lower tPTEF: a tPTEF <0.17 s (below the 25th percentile) was chosen, as lower values have previously found in infants and children with airway obstruction and asthma [39][40][41].…”
Section: Secondary Outcomementioning
confidence: 99%
See 2 more Smart Citations